A Systematic Review of the Consequences of Stigma and Stereotype Threat for Individuals With Specific Learning Disabilities. (May 2023) - Haft, Stephanie L.; Greiner de Magalhães, Caroline; Hoeft, Fumiko
Exposure to stigma and stereotype threat is detrimental for numerous marginalized groups. Research has demonstrated that individuals with specific learning disabilities (SLDs) are vulnerable to stigmatization. The purpose of this systematic review was to summarize the studies investigating associations between SLD-related stigma and stereotype threat and psychological and academic outcomes in individuals with SLDs, as well as examine the overall effect size of these associations across studies. A total of 16 studies met inclusion criteria—12 studies (52 effect sizes) examined SLD stigma with psychological adjustment or academic outcomes, and six studies (eight effect sizes) examined SLD stereotype threat. Greater SLD stigma scores had a medium-sized and significant correlation with less self-esteem across nine effect sizes ( r = −.39, p = .002). Other outcomes were not powered enough for meta-analyses, although studies generally showed that greater SLD stigma and stereotype threat was related to less optimal psychological adjustment. These results suggest that these negative experiences should be a target of intervention and support efforts for individuals with SLDs. The associations between SLD stigma and stereotype threat and academic performance outcomes were comparatively more heterogeneous and less robust. These findings highlight the need for more research on SLD-related stigma and stereotype threat.